2006
DOI: 10.1111/j.1744-7429.2006.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Weaver Ants Increase Premature Loss of Leaves Used for Nest Construction in Rhizophora Trees1

Abstract: Oecophylla ants utilize living leaves when they construct their nests. We investigated how Oecophylla smaragdina nests in southern Thailand affected leaf performance on the mangrove tree Rhizophora mucronata. Leaves used in nests and neighboring leaves showed a higher rate of premature leaf loss compared to control leaves farther from the nests. However, a tree's total cost due to the higher premature leaf loss was estimated to be approximately between 3‐ and 20‐fold lower than the benefit derived from ant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…On the other hand, only 0·25% of the leaves on ant trees were used in ant nests, and the associated costs were estimated to be 6–20 times lower than the benefits gained via a decreased leaf area removed by herbivores (Offenberg et al . , ). Similarly, nest leaves on Benin mango showed reduced leaf longevity, but the number of leaves used in nests was only between 0·42% and 1·2% (Anato et al .…”
Section: Disadvantages (And Their Solutions)mentioning
confidence: 99%
“…On the other hand, only 0·25% of the leaves on ant trees were used in ant nests, and the associated costs were estimated to be 6–20 times lower than the benefits gained via a decreased leaf area removed by herbivores (Offenberg et al . , ). Similarly, nest leaves on Benin mango showed reduced leaf longevity, but the number of leaves used in nests was only between 0·42% and 1·2% (Anato et al .…”
Section: Disadvantages (And Their Solutions)mentioning
confidence: 99%
“…Similarly, Offenberg et al (2006) observed that O. smaragdina showed a strong preference for young leaves on R. mucronata in a Thai mangrove. On the other hand, there was no size difference between the control leaves on nest and control shoots, showing that the nests did not affect the size of neighboring leaves.…”
Section: Discussionmentioning
confidence: 93%
“…Firstly, the number of leaves used to form nests was low, 0.7% in average. Similarly, Offenberg et al (2006) estimated that, O. smaragdina used as little as 0.25% of the leaves of the mangrove tree R. mucronata to form their nest. Thus, weaver ants in general use only few of the available leaves on trees to build their nests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, according to Offenberg et al (2006) weaver ants has a preference to use first position leaves for nest building because these leaves are still expanding and therefore smaller and more flexible than the older leaves and also more likely to host trophobionts. The characteristics of host plant leaves are therefore an important factor in the choice of nesting site.…”
mentioning
confidence: 99%